Phosphoproteomic Analysis Reveals Rio1-Related Protein Phosphorylation Changes in Response to UV Irradiation in Sulfolobus islandicus REY15A - Huang, Qihong; Lin, Zijia; Wu, Pengju; Ni, Jinfeng; Shen, Yulong (Frontiers in Microbiology, 2020)
DNA damage response (DDR) in eukaryotes is largely regulated by protein phosphorylation. In archaea, many proteins are phosphorylated, however, it is unclear how the cells respond to DNA damage through global protein phosphorylation. We previously found that Δrio1, a Rio1 kinase homolog deletion strain of Sulfolobus islandicus REY15A, was sensitive to UV irradiation. In this study, we showed that Δrio1 grew faster than the wild type. Quantitative phosphoproteomic analysis of the wild type and Δrio1, untreated and irradiated with UV irradiation, revealed 562 phosphorylated sites (with a Ser/Thr/Tyr ratio of 65.3%/23.8%/10.9%) of 333 proteins in total. The phosphorylation levels of 35 sites of 30 proteins changed with > 1.3-fold in the wild-type strain upon UV irradiation. Interestingly, more than half of the UV-induced changes in the wild type did not occur in the Δrio1 strain, which were mainly associated with proteins synthesis and turnover. In addition, a protein kinase and several transcriptional regulators were differentially phosphorylated after UV treatment, and some of the changes were dependent on Rio1. Finally, many proteins involved in various cellular metabolisms exhibited Riol-related and UV-independent phosphorylation changes. Our results suggest that Rio1 is involved in the regulation of protein recycling and signal transduction in response to UV irradiation, and plays regulatory roles in multiple cellular processes in S. islandicus.